Middleware-Driven Hybrid Integration: Bridging the Gap in Modern Enterprise Architecture - Suman Neela, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The evolution of middleware-driven hybrid integration has become crucial in modern enterprise architecture, bridging traditional on-premise systems with cloud-native solutions. This transformation addresses the growing complexity of enterprise systems through sophisticated integration patterns and frameworks. Organizations are increasingly adopting middleware solutions to enhance operational efficiency, improve data synchronization, and maintain system reliability across diverse technological landscapes. The implementation of these solutions encompasses comprehensive security frameworks, real-time processing capabilities, and business intelligence integration, enabling organizations to achieve greater agility and competitive advantage in the digital ecosystem. Through service-oriented architectures and advanced integration patterns, middleware solutions facilitate seamless communication between legacy systems and modern cloud platforms while ensuring data consistency and system performance.
Keywords: Cloud-native integration; Digital transformation; Enterprise architecture; Middleware solutions; Service-oriented computing